Melothesia in Babylonia : medicine, magic, and astrology in the ancient Near East - Geller, Markham J. (Boston : De Gruyter, 2014)
This book examines the Babylonian backgroundof melothesia, the science of charting zodiac influences on the human body, which transformed older divination by connecting astrology with medical techniques. Special attention is given to a text from late-5th-century Uruk, which is argued to be an important representative of this new approach to the healing arts, previously only known from Greek and medieval astrology.
Introduction: globalisation of knowledge -- The Uruk taxonomy (SBTU I 43) -- Uruk astral magic (BRM 4 20 and BRM 4 19) -- The Neo-Assyrian precursor: before the zodiac -- Ancient Aramaic and Greek parallels -- Astrological interpretation of SBTU I 43 -- Melothesia -- Concluding hypothesis.
Print version record.
Includes bibliographical references and index.
Master record variable field(s) change: 082
Keywords: Medicine, Assyro-Babylonian.; Astrology, Assyro-Babylonian.; Medical astrology; TRAVEL -- South America -- General; Astrology, Assyro-Babylonian.; Medical astrology; Medicine, Assyro-Babylonian.; Electronic books